Pengembangan Manajemen Talenta Terhadap Kualitas Dan Kinerja Karyawan Sebagai Variabel Performa Di Line Press dan Assymbly “PT. Tatsuya Perkasa Singara.” - Machmud, Pajar (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This study aims to determine the development of talent management for service quality with karaywan performance as an intervening variable at PT. TATSUYA PERKASA SINGARA. The sampling technique used was questionnaires, interviews and observations. The population in this study amounted to 105 people, with a total sample of 51 employees with simple random sampling technique. Data analysis used validity and reliability test, classic assumption test, normality test, multicolonirity test, heterocodasticity test, multiple regression analysis and t test and F test and path analysis test. The analysis used in this study is quantitative and qualitative analysis, in which the analysis uses SPSS version 20.0. The results of this study prove six things, namely, first, that there is a negative and significant effect between recruitment on employee performance. Second, there is a positive and significant influence between training on employee performance. Third, there is a negative and significant effect between compensation for employee performance, fourth, that there is a negative and significant influence between competency on employee performance. Fifth, there is a positive and significant influence between recruitment, training, compensation, and competence on employee performance. Sixth, there is a positive and significant influence between employee performance on service quality.